Dampak Pembangunan Infrakstuktur terhadap Lingkungan dan Kehidupan Masyarakat - Sadikin, Gelby Nuranisa; Syaharani, Riffi Aulia; Johari, Gifani Sri; Azizah, Siti Amalia; Dewi, Anti Maula; Salsabila, Najwa Naila; Vadhilah, Vina; I, Iryanudin; Herdiana, Dian (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Infrastructure development in Indonesia plays a crucial role in accelerating economic growth and improving the quality of life for society. However, infrastructure projects often bring negative impacts on both the environment and social aspects. The aim of this article is to analyze the importance of sustainable infrastructure development and the ways to achieve it. This research uses a descriptive qualitative method with literature study to gather data from various sources. The findings show that sustainable infrastructure development should consider the balance between economy, environment, and social aspects, while also involving public participation and strengthening regulations to achieve the Sustainable Development Goals. This article recommends the need for more inclusive and environmentally-friendly policies in every infrastructure project.